ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI PEMBAYARAN BIAYA PENDIDIKAN BERBASIS WEB DAN SMS GATEWAY PADA PONDOK PESANTREN NURUL IMAN MUARO SEBAPO - Ahadi, Ahmad Husna; Effiyaldi, Effiyaldi (LPPM Universitas Dinamika Bangsa, 2019)
Pondok Pesantren Nurul Iman is a religious education institution that has a number of santri as 621people. In the administrative activities of the payment education fees at Pondok Pesantren Nurul Imanstill use manual recording system that experienced various obstacles such as the length of time required toget information on payment of education fee and often the information is not up to the parents of thesantri. Therefore, need a tool in the form of Information Administration System Payments Education Feethat work in computerized, so that can be a solution of the problem. In this research, system design usingUML modeling that produce use case diagram, activity diagram and class diagram. The results of thisresearch is a prototype of the Information System Administration Payment Education Fees based web andSMS Gateway in the hope to help overcome the problems that occur